Difficulties and strategies of learning English reading skills in large classes: A systematic literature review - Santi Istiqomah; Rohmani Nur Indah; Edwin Nuvianto Al Aziz (Journal of English Language Teaching and Learning (JETLE), 2023)
Reading in large classes can lead to many difficulties demanding for various teaching strategies to overcome any difficulties. This research aimed to find the difficulties found in large classes of reading and analyzed the strategies used to overcome them. It used a systematic analysis method that identifies existing literature available online. The data collection was carried out through systematic literature review stages: 1) framing questions for a review, 2) identifying relevant work, 3) assessing the quality of studies, 4) summarizing the evidence, and 5) interpreting the findings. The results show that students learning English in large classes particularly in secondary schools are always constrained in making inference, finding main idea, retention of detail information, understanding vocabulary, and locating reference. Concerning the strategies, junior and senior high school students must be involved in joyful and meaningful group fun activities forreading. However, at university level, the self and autonomous learning style must be implemented. The finding implies on the need for collaborative learning method and also group fun activities for reading. It can be also helped by utilizing the technology and digital platform to make the students have more experiences inlearning reading in large class.